Answer:
100+3, a hundred three.
Step-by-step explanation:
The left side
1.99999925
1.99999925
does not equal to the right side
1
1
, which means that the given statement is false.
Answer:
30p^3−36p
Step-by-step explanation:
6(5p^3−6p)
=(6)(5p^3+−6p)
=(6)(5p^3)+(6)(−6p)
=30p3−36p
B since you can rewrite it as (2x+7)(x-4)=0 and you can solve it and you get B
Answer:
1
Step-by-step explanation:
The function with the given zeros will factor as ...
f(x) = a(x +15)(x^2 +9) . . . . with leading coefficient 'a'
You have ...
f(2) = 221 = a(2+15)(2^2+9) = a(17)(13) = 221a
Then a = 221/221 = 1
The leading coefficient is 1.
_____
<em>Additional comment</em>
As you know, a function with zero x=p has a factor of (x -p). The given zeros mean the function has factors (x -(-15)), (x -3i). and (x -(-3i)). The product of the last two factors is the difference of squares: (x^2 -(3i)^2) = (x^2 -(-9)) = (x^2 +9). This is how we arrived at the factorization shown above.